Locoregional Control and Survival in Children, Adolescents, and Young Adults With Localized Head and Neck Alveolar Rhabdomyosarcoma—The French Experience - Machavoine, Roxane; Helfre, Sylvie; Bernier, Valérie; Bolle, Stéphanie; Leseur, Julie; Corradini, Nadège; Rome, Angélique; Defachelles, Anne-Sophie; Deneuve, Sophie; Bernard, Sophie; Fayoux, Pierre; Nicollas, Richard; et al. (Frontiers in Pediatrics, 2022)
Introduction Head and Neck (HN) is the most frequent site of pediatric rhabdomyosarcoma (RMS). Alveolar RMS (ARMS) represent 20% of all RMS cases and frequently spread to lymph nodes. The aim was to report locoregional control, event-free survival (EFS) and overall survival (OS), according to clinical and pathological features, lymph nodes (LN) staging, and treatment modalities. Methods The study included all patients prospectively enrolled in EpSSG RMS 2005 study under 21 years of age with localized HN ARMS and diagnosed between 2005 and 2016 in France. Medical data including imaging, surgical report, and radiation therapy planes were analyzed. Results Forty-eight patients (median age: 6 years; range 4 months-21 years), corresponding to 30 parameningeal and 18 non-parameningeal ARMS, were included. There were 33 boys (69%). Tumor locations included: orbit (n=7) among which 4 cases with bone erosion, paranasal sinuses and nasal cavity (n=16), deep facial spaces (n=10), nasolabial fold (n=8) and others non parameningeal HN site (n=7). A fusion transcript of PAX3-FOXO1 or PAX7-FOXO1 was expressed in 33 of the 45 cases (73%) with molecular analysis. At diagnosis, 10 patients had primary resection of primary tumor (PRPT) (none with microscopic complete resection) and 9 had LN staging. After induction chemotherapy, 26 patients (54%) had secondary resection of primary tumor (SRPT) and 13 patients (27%) had cervical LN dissection. 43 patients (90%) were treated with radiation therapy. With a median follow-up of 7 years (range 2-13 years), five-year OS and EFS were 78% (95%CI, 63%-88%) and 66% (95%CI, 51%-78%), respectively. We observed 16 events (10 deaths): 4 local, 4 regional, 1 local and regional, and 7 metastatic. In univariate analysis, OS was only superior for patients under 10 years of age (p=0.002) while FOXO1-negative ARMS, SRPT for parameningeal ARMS and lymph node surgery were associated with significantly better EFS. Survival rates were not correlated with any other clinical parameters or treatment modalities. Conclusion Our study confirms better outcome of ARMS in children under 10 years of fusion-negative cases. Moreover, lymph node surgery and SRPT of parameningeal tumor may improve EFS of ARMS.